Programming shared virtual memory multiprocessors - Gerndt, M. (Parallel and Distributed Processing, 4th Euromicro Workshop on (PDP '96, 1996)
Highly parallel machines needed to solve compute intensive scientific applications are based on the distribution of physical memory across the compute nodes. The drawback of such systems is the difficult message passing programming model. Therefore, a lot of research in simplifying the programming model is going on. This article investigates the combination of a task parallel programming model implemented on top of a shared virtual address space provided by the operating system of the parallel machine.